DETAILING AND GENERALIZING THE MOTIVES FOR SCIENTIFIC RESEARCH OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS - Notchenko, Viktoriia; Dyatlov, Yuriy (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In the article, the authors paid attention to the issues of identifying and detailing the motives of students of higher educational institutions for scientific research during their studies. Based on the generalization of the opinions of the authors who participated in the development of this problem, and the results of their own research, the authors of this article at the initial stage of the study analyzed and summarized the conclusions of scientists about the totality and detail of the above-mentioned motives. Further, the authors of this article justified a holistic set of interrelated motives that encourage students to engage in scientific research in addition to their current academic and other activities. In the process of studying the motives, the authors identified factors that represent a generalized grouping of motives for students' scientific research. Grouped motives, considered as motivational factors, can generally be considered as forces that encourage students to engage in the type of activity under consideration, namely: scientific research.The motivation factors that the authors reasonably propose to consider as determining the motivation of students for research activities are: the need for self-realization; reflection; social utility; professional interest; remuneration; social interaction; satisfaction from the process and the result. Each of the factors is justified and logically connected with the corresponding motives. This grouping is presented in tabular form and, as mentioned earlier, contains the rationale for the elements included in it.The identified factors and related motives can serve as a basis for the development of a survey material to assess students ' motivation for research activities.